Preventing stunting among adolescents by increasing knowledge and awareness of local food utilization - Nur Aini Mahmudah; Nur Agustin Mardiana; Aditya Wirawantoro Putra; Panji Purnomo; Anang Widigdyo; David Kurniawan (Journal of Community Service and Empowerment, 2024)
Stunting remains a critical public health issue in Indonesia. The "Acceleration of Stunting Reduction" program is targeting adolescents (teenagers) as one of its key groups. This reflects the understanding that adolescents play a vital role in overcoming the problem of stunting, both as parents-to-be and as individuals who can experience the negative impact of malnutrition, which in turn contributes to the incidence of stunting. This study exposing the effectiveness of educational interventions in improving adolescent knowledge and awareness about stunting and the utilization of local foods as preventive measures. Conducted at State Senior High School of Kademangan (SMKN 1 Kademangan), Blitar, the study involved 101 eleventh-grade students who participated in a series of counselling (educational sessions) on topic stunting and local food utilization. A pretest-posttest design was used to assess changes in knowledge across seven key areas related to stunting and nutrition. The results indicated substantial improvements in understanding, with knowledge increases ranging from 37% to 58% across all areas. These findings underscore the importance of targeted nutritional education in enhancing adolescent health literacy. Ongoing educational sessions, practical activities, and further research are recommended to sustain and build upon these gains, ultimately contributing to the reduction of stunting prevalence in Indonesia.